Tantangan, Problematika dan Peluang Pembelajaran Pendidikan Agama Islam di Perguruan Tinggi - Erwin Muslimin; Uus Ruswandi (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2022)
We know that our country Indonesia is a country where the majority of the population is Muslim. However, in terms of education, Islamic education is seen as always in the second row in the national education system. In fact, in essence, any education, both national education and Islamic education, has the same goal, namely to humanize humans so that they are truly capable of becoming caliphs on earth. This indicates to us that Islamic education in Indonesia is still wrapped in a number of problems. The existence of a problem is certainly rooted in external causes and internal causes. Likewise with Islamic education, internal and external problems are also present in the midst of Islamic education. Starting from internal problems such as those related to management to external problems such as politics and economics. All of them have added to the list of problems that we should be addressing. Sometimes we find internal problems that attack Islamic education, including those that lie in the education management that is applied, or sometimes we find the management of Islamic education that is not clear about the goals to be achieved, or the lack of qualified and professional educators. Keywords: Challenges, Problems, Opportunities, Learning, Islamic Religious Education, Higher Education